Phosphoinositide 3-kinase in Health and Disease Volume 1 - Rommel, Christian; Vanhaesebroeck, Bart.; Vogt, Peter K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
From humble beginnings over 25 years ago as a lipid kinase activity associated with certain oncoproteins, PI3K (phosphoinositide 3-kinase) has been catapulted to the forefront of drug development in cancer, immunity and thrombosis, with the first clinical trials of PI3K pathway inhibitors now in progress. Here the authors give a brief overview of some key discoveries in the PI3K area and their impact, and include thoughts on the current state of the field, and where it could go from here.
PI3K – From the Bench to the Clinic and Back -- PI3K Book Introduction -- PDK1: The major transducer of PI 3-Kinase actions -- Protein Kinase B (PKB/Akt), a key mediator of the PI3K signaling pathway -- Regulatory subunits of class IA PI3K -- The Regulation of Class IA PI 3-kinases by Inter-Subunit Interactions -- Phosphoinositide signalling pathways in metabolic regulation -- Role of RAS in the regulation of PI 3-kinase -- More than just kinases: The scaffolding function of PI3K -- PI3K signalling in neutrophils -- PI 3-kinase p110beta regulation of platelet integrin alphaIIbbeta3 -- PI3Ks in lymphocyte signalling and development -- PI3 kinase regulation of skeletal muscle hypertrophy and atrophy -- Taking PI3Kdelta and PI3Kgamma one step ahead – Dual active PI3Kdelta/gamma inhibitors for the treatment of immune-mediated inflammatory diseases -- Oncogenic Mutations of PIK3CA in Human Cancers -- Structural Effects of Oncogenic PI3Kalpha Mutations -- Comparing the roles of the p110alpha and p110beta isoforms of PI3K in signaling and cancer -- Phosphatidylinositol 3-kinase (PI3K): The oncoprotein -- AKT Signaling in Physiology and Disease -- Faithfull modeling of PTEN loss driven diseases in the mouse -- PI3K as a target for therapy in haematological malignancies -- Clinical development of Phosphatidylinositol-3 kinase pathway inhibitors -- New inhibitors of the PI3K-Akt-mTOR pathway: Insights into mTOR signaling from a new generation of Tor kinase domain inhibitors (TORKinibs) -- Small molecule inhibitors of the PI3-kinase family -- Targeting the RTK-PI3K-mTOR axis in malignant glioma: overcoming resistance -- Subject index.
Keywords: Cancer research; Human physiology; Molecular biology; Cancer Research; Human Physiology; Molecular Medicine